Postcolonial minoritarian characters : transformative strategies for re-mediating raced marginalisation in South African English fiction - Misbach, Abdul Waghied (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.